The Effect of Institutional Ownership, Capital Structure, Dividend Policy, and Company Growth on Company Value: Pengaruh Kepemilikan Institusional, Struktur Modal, Kebijakan Dividen, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Reza Mulia Sari; Dina Patrisia (Perkumpulan Doktor Indonesia Maju, 2020)
This paper aims to examine wheter there is significant institusional ownership, capital structure, dividen policy and company’s growth to firm value. This paper also aims to examine wheter variabel of company’s growth could be moderating this study. Sample of this study uses purposive sampling method in order to obtain a final sample accounting 36 companies with observation period from 2012-2017. Type of data in this study secondary data and uses in multiple linier regression as an analytical tool. The result of this study indicate that institusional ownership has no effect on firm value. Capital structure, dividend policy and company growth have a positive effect on firm value. Corporate growth cannot moderate the reationship between institusional ownership and firm value. Corporate growth weakens the relationship between capital structure and firm value. Corporate growth cannot moderate the relationship between dividend policy and firm value.